The relationship between training characteristics and durability in professional cyclists across a competitive season - Spragg, J.; Leo, P.; Swart, J. (European Journal of Sport Science, 2023)
This study investigated the influence of training characteristics on the fatigued power profile in professional cyclists. Data was collected from 30 under 23 professional cyclists (age: 20.1 ± 1.1 years, body mass: 69 ± 6.9 kg, height: 182.6 ± 6.2 cm, VO2max: 73.8 ± 2.5 mL/kg/min, CP: 5.48 ± 0.38 W/kg, W´: 17.83 ± 3.57 kJ) across a competitive season and collated in to 3 periods: early-, mid- and late-season. Two power profiles (fresh and fatigued) were created from absolute (W) and relative (W/kg) 2-, 5-, and 12-min maximal mean power outputs. The fresh power profile consisted exclusively of power output values produced prior to 2000 kJ work (2MMPfresh, 5MMPfresh and 12MMPfresh) while the fatigued power profile consisted of power output values produced exclusively post 2000 kJ (2MMPfatigue 5MMPfatigue and 12MMPfatigue). Training characteristics were analysed to assess their influence on the power profiles. Absolute 5MMPfatigue, 12MMPfatigue and relative 12MMPfatigue were significantly lower in late-season compared with early- and mid-season (p < 0.05). The difference in absolute 12MMPfresh and 12MMPfatigue was significantly greater in late than in early- and mid-season. A significant relationship was found between training time below the first ventilatory threshold (Time < VT1) and improvements in absolute and relative 2MMPfatigue (r = 0.43 p = 0.018 and r = 0.376 p = 0.04 respectively); and between a shift towards a polarized training intensity distribution and improvements in absolute and relative 12MMPfatigue (r = 0.414 p = 0.023 for both) between subsequent periods. In conclusion, there is greater variability in the fatigue power profile across a competitive season than the fresh power profile.